Factors influencing the response to 1alpha-hydroxyvitamin D3 in patients with renal bone disease. - Kanis, J; Russell, R; Naik, R; Earnshaw, M; Smith, R; Heynen, G; Woods, C (1977)
Twenty-three patients with bone disease and chronic renal failure were treated for periods of 4--28 months with 1alpha-hydroxyvitamin D3 (1alpha-OHD3). Improvements in bone histology were consistently seen in patients with features both of osteitis fibrosa and osteomalacia but were not invariably observed in patients with osteitis fibrosa or osteomalacia alone (37 and 50% improved respectively). Several factors influencing the outcome of treatment were assessed on the basis of histological responses in bone. A low level of plasma calcium before treatment, rather than the dose of 1alpha-OHD3 tolerated, was the major detectable factor which favourably affected the histological outcome. Other factors examined, including initial plasma concentrations of phosphate, immunoreactive parathyroid hormone and alkaline phosphatase, and treatment with haemodialysis or dietary supplements of calcium did not apparently influence the response.